Phylogeographical structure of the boreal‐montane orchid Malaxis monophyllos as a result of multi‐directional gene flow. (19th March 2015) - Jermakowicz, Edyta; Wróblewska, Ada; Brzosko, Emilia; Mirski, Paweł; Hirse, Toomas
<x xml:space="preserve">Abstract</x> We investigated the phylogeographical structure of the boreal‐montane orchid Malaxis monophyllos in its Eurasian geographical range. We analysed four sequences of plastid DNA (trnL, trnL–trnF, rps16 and accD‐psaI), resulting in 19 haplotypes and revealing a high level of intraspecific diversity (HD = 0.702 and π = 0.196 × 10−2), but showing a lack of phylogeographical structure. This pattern might be caused by multiple phenomena and processes, e.g. broad‐fronted recolonization with accompanying multi‐directional gene flow between populations and expansion from at least two refugial areas. Despite the lack of phylogeographical structure, three centres of haplotype diversity were indicated in the European part of the range of M. monophyllos. According to these data, alpine and lowland glacial refugia located between the ice sheets in the European Alps and the Scandinavian glaciers seem most likely to be in Europe. Moreover, models of climatically suitable areas during the Last Glacial Maximum (LGM) confirmed the Alps as a possible refuge, and indicated an opportunity for the persistence of M. monophyllos populations in Beringia and parts of Siberia. Using two models [Model for Interdisciplinary Research on Climate (MIROC) and Community Climate System Model (CCSM)], we predicted a significant reduction in climatically suitable areas for M. monophyllos in the future (2080). Our study also demonstrated that the biological features of M. monophyllos, including breeding system and dispersal mode, seem to be crucial in understanding its phylogeographical pattern. Our results also highlighted the importance of anthropogenic habitats as reservoirs of genetic diversity and alternative habitats for this species in the context of declining natural populations. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 178, 138–154.